Microbial counts in hands with and without nail varnish after surgical skin preparation: a randomized control trial. (October 2018) - Kulkarni, Vinay; Murray, Anthony; Mittal, Rajat; Spence, David; O'Kane, Gabrielle; Incoll, Ian
Nail varnish is commonly removed from fingernails prior to surgical procedures. We report the results of a randomized controlled trial comparing the microbial counts in hands with and without nail varnish applied, following surgical skin preparation. Forty-three patients were randomized; three patients were lost to follow-up. Each patient had one hand painted with nail varnish and had both hands tested 1 week later. There was no significant difference in terms of positive microbial growth between the nail plates or hyponichia with or without nail varnish applied. Our results demonstrate that the presence of nail varnish does not have an effect on the microbial counts of hands following surgical skin preparation. Level of evidence: I